Efficient solving of engineering design problems by an interior point 3-D filter line search method - Costa, M. Fernanda P. (2008)
Here we present an interior point three-D filter line search method for solving optimization problems. Each entry in the filter includes the feasibility measure, the centrality measure and the barrier objective function value. The algorithm is tested with benchmark engineering design problems, and a comparison with other published results are also included.